Intensity of pest attack and yield of potato plant during offseason in Sajang Village, Sembalun District, West Lombok. Issue 1 (November 2021) - Sarjan, M; Jihadi, A; Kisman,; Nikmatullah, A
Abstract: Pests and diseases attacks are major limitation for white potato ( Solanum tuberosum L.) production, and therefore intensive treatments are employed during the cultivation. There is an increasing constraint of the intensive pest control to sustainable potato production and environmental impacts; therefore it is crucial to select suitable cultivar, particularly for the rainy, off-season cultivation, at which production is scared. This research evaluated the intensity of pest attack and yield of two variety of white potato, designated as cv. Chitra and Atlantic, during rainy season. Experiment was conducted in Sajang Village, of Sembalun District, West Nusa Tenggara from March to June 2021. In the field, the plants were maintained according to common maintenance employed farmer in Sembalun, and data collected at two weekly basis. The results showed that symptom of pest attached was visible since the plants was 4 weeks old with no real different intensity between the two variety. A higher rate of pest intensity was recorded in Chitra variety compared to the Atlantic. However, the yield of the two varietie was not differing significantly. The results indicated that the two varieties could be cultivated during off-season and insects are not a major problem during offseason that limits potato plant growth and production in Sajang Village. Further study is needed to evaluate the potential cultivation of the two varieties whole year.